If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + -1(2x + -4) = 4 + -3x Reorder the terms: 9 + -1(-4 + 2x) = 4 + -3x 9 + (-4 * -1 + 2x * -1) = 4 + -3x 9 + (4 + -2x) = 4 + -3x Combine like terms: 9 + 4 = 13 13 + -2x = 4 + -3x Solving 13 + -2x = 4 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 13 + -2x + 3x = 4 + -3x + 3x Combine like terms: -2x + 3x = 1x 13 + 1x = 4 + -3x + 3x Combine like terms: -3x + 3x = 0 13 + 1x = 4 + 0 13 + 1x = 4 Add '-13' to each side of the equation. 13 + -13 + 1x = 4 + -13 Combine like terms: 13 + -13 = 0 0 + 1x = 4 + -13 1x = 4 + -13 Combine like terms: 4 + -13 = -9 1x = -9 Divide each side by '1'. x = -9 Simplifying x = -9
| (-125n^3x^5z^4)^2/(75n^4x^5z^9)^2 | | 66(6x+0.5)=5x-66 | | X/2-5/6y=1/3 | | y+6=11 | | -95=-3(-7r+1)-8 | | -6n+4n=12 | | y=2x+100 | | 5=2x+3(9x+1) | | 2p+1-8=-9 | | 6-i/2i | | 7-3x-8x=-4 | | 25x^2+56x+4=5 | | 6-3x-8x=-4 | | 5v-9=66 | | 5p-2q=17 | | Y^2+12x-4y-8=0 | | 5p-2q=7 | | (6-x)(4-x)=30 | | 6z-8z+3=0 | | (6-x)x(4-x)=30 | | n-2/2=-7 | | 17.6=2.2*n | | 210=3(-7x-2)-6x | | kx^2+10x-8=0 | | 2p-q=7 | | -4(-7n+5)=1 | | 1/2(x+3)^2=5 | | 0.5x+4=0.75(2x-8) | | 7n=-77 | | -21=56 | | 6-6x+4=4 | | 1/2(x+3)2=5 |